2006
DOI: 10.1007/s11205-005-4127-5
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Perceived Spirituality, Religiosity, and Life Satisfaction: The Mediating Role of Self-Rated Health

Abstract: life satisfaction, quality of life, religiosity, spirituality,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
95
0
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(116 citation statements)
references
References 61 publications
12
95
0
9
Order By: Relevance
“…They found a moderate effect size (r = 0.34, 95% CI: 0.28-0.40) and concluded that the results of the meta-analysis support the conceptualization of spirituality as a distinct concept that relates to quality of life. Zullig et al [100] stated that several studies have suggested that religiosity and spirituality have a significant effect on measures of QOL, even when controlling for sociodemographic variables. However, a limited number of studies has been explored this relation among college students.…”
Section: Associations Among Qol Swb and Religiositymentioning
confidence: 99%
See 1 more Smart Citation
“…They found a moderate effect size (r = 0.34, 95% CI: 0.28-0.40) and concluded that the results of the meta-analysis support the conceptualization of spirituality as a distinct concept that relates to quality of life. Zullig et al [100] stated that several studies have suggested that religiosity and spirituality have a significant effect on measures of QOL, even when controlling for sociodemographic variables. However, a limited number of studies has been explored this relation among college students.…”
Section: Associations Among Qol Swb and Religiositymentioning
confidence: 99%
“…The correlations ranged between moderate and high, suggesting the single item measure could serve as a substitution for the multiple item scale. Zullig et al [100] quoted several studies to support the merit of the single question to assess health. They stated that an extensive body of literature supports self-perceived health as predictive of mortality, morbidity, risk behavior in adults, and with personal, behavioral, and psychological factors, e.g., health problems, disability, age, female gender, income, smoking, and higher BMI in adolescents.…”
Section: Self-rating Scalesmentioning
confidence: 99%
“…Among these positive youth development constructs, many were found to associate with life satisfaction: Paxton et al (2006) showed that bonding to adults and owning meaningful social roles were closely related to adolescent life satisfaction; Stein and Newcomb (1999) reported that intimate relationships formed in early adulthood contributed to life satisfaction in later adulthood; Ciarrochi et al (2003) found that social and emotional competencies were significant predictors of life satisfaction. Academic and social self-efficacy (Vecchio et al 2007), prosocial motivation and behaviour (Caprara and Steca 2005;Gebauer et al 2008), spirituality and religiosity (Laudet and White 2008;Zullig et al 2006), as well as mastery and ethnic identity (Sam 1998) were also found to be significant predictors of life satisfaction. In sum, using Catalano et al's (2004) definition of positive youth development, the above studies demonstrate that positive youth development predicts life satisfaction.…”
mentioning
confidence: 96%
“…Meanwhile, religiosity increases happiness, and happy people are more willing to also help others (Pessi, 2011). The relationships between religious belief and well-being are generally found to be positive (Cohen, 2002;Tiliouine, Cummins, & Davern, 2009;Zullig, Ward, & Horn, 2006). Personal well-being, one of the concepts that express the eudemonic approach, shows a positive relationship with spirituality (Wills, 2009).…”
Section: Social Virtuesmentioning
confidence: 99%